ARTISTIC FEATURES AND PROSPECTS OF UZBEK POTTERY SCHOOLS - Akbaralieva Maftuna Abdumannob qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article examines the artistic characteristics and developmental prospects of Uzbek schools of pottery art. As one of the oldest cultural traditions in Central Asia, Uzbek pottery represents a unique synthesis of regional aesthetics, craftsmanship, and historical continuity. The paper analyzes the stylistic differences between Rishtan, Gijduvon, Khiva, Samarkand, Shahrisabz, and Tashkent pottery schools. It also discusses technological innovations, the influence of natural resources such as clay deposits and mineral pigments, market dynamics, and cultural heritage preservation policies. Based on literature review and comparative analysis, the study identifies key developmental challenges and future opportunities for enhancing local pottery craftsmanship and supporting artisans in the global market.